Impact of Research Output in Finance on Financial Development: Empirical Investigation from Middle Eastern Economies - C. Azmeh; M. Al-Raeei (Финансы: теория и практика)
The primary purpose of the study is to evaluate the impact of research output in finance, both in terms of quantity and quality, on the development of the financial sector. The study analyzed data from 2000 to 2017, including 15 countries in the Middle East, employing a two-step SYS-GMM method. The empirical findings reveal a significant correlation between the quantity of research output in finance and the overall activity and stability of the financial sector. However, when it comes to the quality of research output in finance, it only positively influences the activity while negatively and significantly affecting the stability of the financial sector. This noteworthy result suggests that highly regarded research in finance may recommend taking greater risks for national reforms, operating under the belief of “no pain, no gain”. High-quality research in finance often offers valuable insights, minimizes risk and uncertainty, and helps inform policies and reform strategies for successful implementation. It is crucial for Middle Eastern policymakers to prioritize improving both the quantity and quality of finance research and provide support to researchers. This will enable them to achieve the desired economic growth and impact the development of the financial sector. Furthermore, policymakers can also consider recommendations from well-respected economists to mitigate instability in the financial sector while pursuing necessary, albeit risky, initiatives for successful reform. To date, no other research has investigated the influence of research output in the field of finance on financial development, both in terms of quantity and quality.